2011
DOI: 10.1002/cncr.25900
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival after radical prostatectomy versus external‐beam radiotherapy for patients with high‐risk prostate cancer

Abstract: BACKGROUND:The long-term survival of patients with high-risk prostate cancer was compared after radical prostatectomy (RRP) and after external beam radiation therapy (EBRT) with or without adjuvant androgen-deprivation therapy (ADT). METHODS: In total, 1238 patients underwent RRP, and 609 patients received with EBRT (344 received EBRT plus ADT, and 265 received EBRT alone) between 1988 and 2004 who had a pretreatment prostate-specific antigen (PSA) level 20 ng/mL, a biopsy Gleason score between 8 and 10, or cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(170 citation statements)
references
References 41 publications
11
152
0
7
Order By: Relevance
“…[4][5][6][7] On the other hand, large retrospective studies with long followup times demonstrated equivalence of RP to RT + ADT. [8][9][10][21][22][23][24][25][26] A meta-analysis showed a modest improvement in cancer-specific survival with RP compared to RT + ADT. 21 However, this finding was based on two small retrospective studies and the authors of the meta-analysis were concerned about the limited quality of most studies included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] On the other hand, large retrospective studies with long followup times demonstrated equivalence of RP to RT + ADT. [8][9][10][21][22][23][24][25][26] A meta-analysis showed a modest improvement in cancer-specific survival with RP compared to RT + ADT. 21 However, this finding was based on two small retrospective studies and the authors of the meta-analysis were concerned about the limited quality of most studies included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In contrast, Boorjian et al reported similar 10-year cancer-specific survival in patients treated with RP or RT + ADT. 8 Overall, the retrospective data that compared outcomes of RP to RT + ADT suffered from selection bias, variable length of ADT use, and contamination of the RP cohort by adjuvant and salvage therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One was a randomized controlled clinical trial, and the remaining were observational studies. Based on the GRADE system, 93% (13 observational of 14) of the studies were considered to have a low level of confidence in quality (4,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Table 2 lists the 14 studies in chronologic order, the RS assigned to each, and the scoring of each individual component.…”
Section: Resultsmentioning
confidence: 99%
“…En l'absence de séries comparatives et randomisées, les résultats de la PT avec ou sans traitement adjuvant apparaissent superposables, dans une population sélectionnée de patients, à l'association radiothéra-pie-hormonothérapie en termes de survie sans récidive biologique et de survie spécifique et globale [4,6,13,14,34]. La morbidité de la PT dans les tumeurs à haut risque semble comparable à celle de la PT pour les tumeurs localisées, lorsqu'elle est réalisée par un chirurgien expérimenté [4,6,14,30,34].…”
Section: éValuation Osseuseunclassified